THE TULUDE TRADITION IN LONDOUN VILLAGE, EAST POPAYATO DISTRICT, POHUWATO REGENCY - Rasyid, Meyranti; Manay, Helman; Arrazaq, Naufal Raffi; Tasnur, Irvan (Satmata: Journal of Historical Education Studies, 2025)
This study aims to describe the implementation, meaning, and role of the Tulude tradition in the life of the people of Londoun Village, Popayato Timur Sub-district, Pohuwato Regency. The research employed a descriptive qualitative approach, using in-depth interviews and documentation as data collection techniques. The results show that Tulude is an annual traditional ceremony held on January 31st as an expression of gratitude, a prayer for protection, and a ritual to ward off misfortune or disaster. This tradition was brought by the Sangir community during the colonial transmigration era and continues to be preserved today by all levels of society, including the younger generation. Tulude also serves as a medium for strengthening cultural identity, social solidarity, and integration among residents in a multicultural society. Cultural symbols such as the tamo, communal prayers, and traditional attire play a central role in the ritual. Challenges such as declining youth interest and the influence of modern culture are addressed through the active involvement of traditional leaders, community groups, and support from educational institutions and the village government. The Tulude tradition has high cultural value and holds strong potential to be continuously preserved as part of local cultural heritage.